Training on the utilization of banana pseudostems for manufacturing liquid organic fertilizer - Murnita Murnita; Afrida Afrida (Universitas Ahmad Dahlan, Yogyakarta, 2021)
Tanjung Durian Pasar Baru village, Bayang subdistrict, Pesisir Selatan district is one of the location for the Students Community Service - Community Empowerment Learning Ekasakti University in 2019. This location is an agricultural area, one of the commodities is the banana plant. The habits of the farmers during this time, banana stems have been cut down are left to rot in the banana groves (waste). Even though banana stem can be used, one of which is for liquid organic fertilizer. Therefore this community service aims to; (1) to increase the farmer's motivation to make liquid organic fertilizer from the fake banana stem, (2) to improve the farmer's knowledge and skills about liquid organic fertilizer from the fake banana stem, and (3) to encourage the farmers to use liquid organic fertilizer from the fake banana stem, to reduce the use of inorganic fertilizer. In order to achieve this objective, the method used is counselling, practice, monitoring and evaluation. The results achieved show that community service activities are going well, and the community is eager to participate in the training and has a high desire to continue making POC, as seen from the activities of making POC which are carried out again by farmers. Farmers' knowledge increased about the understanding, advantages, disadvantages, benefits of POC and dexterity in making and using POC from fake banana stalks above 70%. The community implements the use of POC on peppers and tomatoes, thereby minimizing the use of inorganic fertilizers. In addition, POC can be marketed, thereby increasing farmers' income.